2019
DOI: 10.1038/s41598-019-52540-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential allosteric modulation within dopamine D2R - neurotensin NTS1R and D2R - serotonin 5-HT2AR receptor complexes gives bias to intracellular calcium signalling

Abstract: Proceeding investigations of G protein-coupled receptor (GPCR) heterocomplexes have demonstrated that the dopamine D2 receptor (D2R), one of the hub receptors in the physiology of schizophrenia, interacts with both the neurotensin NTS1 (NTS1R) and the serotonin 5-HT2A receptor (5-HT2AR) in cell lines and rodent brain tissue. In situ proximity ligation assay and BRET-based saturation experiments confirmed interacting receptor assemblies in HEK293T and neuronal HT22 cells. The NTS1R agonist NT(8-13) reduces the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…As for schizophrenia, it is of great interest that serotonin and glutamate interactions have been demonstrated in preclinical models of schizophrenia that, at least in part, take place in 5-HT2AR-mGluR2 heterocomplexes, which affect trafficking and localization involving mouse frontal cortex pyramidal neurons [74,75]. The demonstration of 5-HT2AR-D2R heterocomplexes is also of great relevance for schizophrenia [76][77][78][79], since D2R and 5-HT2AR antagonists represent major drugs in the treatment of schizophrenia. It should be noted that in 2010, a review presented electrophysiological evidence for serotonin-dopamine interactions [73].…”
Section: Implications For a Role Of 5-ht Heteroreceptor Complexes In Other Types Of Brain Disease Besides Depressionmentioning
confidence: 99%
“…As for schizophrenia, it is of great interest that serotonin and glutamate interactions have been demonstrated in preclinical models of schizophrenia that, at least in part, take place in 5-HT2AR-mGluR2 heterocomplexes, which affect trafficking and localization involving mouse frontal cortex pyramidal neurons [74,75]. The demonstration of 5-HT2AR-D2R heterocomplexes is also of great relevance for schizophrenia [76][77][78][79], since D2R and 5-HT2AR antagonists represent major drugs in the treatment of schizophrenia. It should be noted that in 2010, a review presented electrophysiological evidence for serotonin-dopamine interactions [73].…”
Section: Implications For a Role Of 5-ht Heteroreceptor Complexes In Other Types Of Brain Disease Besides Depressionmentioning
confidence: 99%
“…D 2 R-NTSR1 Heterodimerization. Besides its homodimerization, D 2 R is known to interact with GPCRs from different neurotransmitter families, such as serotonin (5-HT 2A R) 27 or adenosine (A 2A R). 7,25 Direct interaction with NTSR1 negatively modulates D 2 R 26,27,33 and is of special interest for neurodegenerative or psychiatric disorders, like Parkinson's disease or schizophrenia.…”
Section: Acs Chemical Biologymentioning
confidence: 99%
“…The anatomical overlap between NT, NTR1 , dopamine, and DRD2 suggests possible interactions that regulate neurophysiological functions at the cellular level. Numerous studies have demonstrated that NT could regulate the affinity of DRs for dopamine and dopamine receptor agonists ( 30 , 32 , 49 51 ), in addition to its action on the excitability of dopaminergic neurons ( 33 , 52 54 ). In the present study, we demonstrated that three NTR1 gene polymorphisms were significantly associated with projective identification and that the rs6011914 polymorphism was significantly associated with reaction formation in healthy Han-Chinese males.…”
Section: Discussionmentioning
confidence: 99%
“…The NTR1 gene is located on the 20q13 locus and consists of four exons and three introns ( 29 ). A large amount of anatomical, physiological, pharmacological and behavioral evidence has demonstrated that NT transmission modulates central dopaminergic functions ( 30 – 33 ). Therefore, the genes of the NT system may contribute to defense mechanisms by regulating dopamine neurotransmission.…”
Section: Introductionmentioning
confidence: 99%